Multi length-scale quantification of hierarchical microstructure in designed microtubular SOFC electrodes - Cooper,SJ; Li,T; Bradley,RS; Li,K; Brandon,NP; Kilner,JA (2015)
The transport properties of a micro-tubular solid oxide fuel cell (MT-SOFC) anode have been analysed by imaging and simulation at multiple length-scales. The anode support investigated was manufactured using a phase inversion-assisted co-extrusion process, which generated a hierarchical and highly anisotropic microstructure. The resulting pore network was observed to contain two distinct, but interacting transport systems. The features in these systems spanned several orders of magnitude and as such it was not possible to image or model them simultaneously. The simulations indicated that the design of the microstructure was beneficial for the radial transport required by these cells; however this conclusion was only obtained by considering diffusive systems at many length-scales.